'Integral Development' or 'Humanistic Prejudice'?: A problematization of suppositions in the social doctrine of the Church (PONTIFICIA UNIV CATOLICA CHILE, FACULTAD TEOLOGIA, 2007)
In the present article, pondering the current applicability of the social doctrine of the Church to the challenges of contemporary society, a fundamental supposition grounding the concept of development is discussed, precisely as it has been conceptually worked from John XXIII onwards. In the social doctrine of the Church, the category of "integral development" not only contains an explicit normative connotation, but also reflects an implicit social theory to the extent that it presupposes a line of continuity between the individual and society. Such a supposition of continuity is contested by one of the most influential of contemporary social theories, that of Niklas Luhmann. The theory of self-referring social systems is based on a true interpellation, if not refutation, of the well-intentioned desires of every normative theory of development (among them, the social doctrine of the Church). From this point the author, rather than attempting an exegesis of the concept in the formulations of the Church's magisterium, investigates its present condition in the context of contemporary social transformations.